Applying Apriori algorithm to explore long-term care services usage status—Variables based on the combination of patients with dementia and their caregivers - Chen, Yen-Jen; Jhang, Kai-Ming; Wang, Wen-Fu; Lin, Guan-Cheng; Yen, Shao-Wei; Wu, Hsin-Hung (Frontiers in Psychology, 2022)
Purpose The aim of this study was to identify the combination of patients with dementia and their caregivers' characteristics associated with long-term care (LTC) services usage. Patients and methods A cross-sectional study was conducted with 475 patients with mild, moderate, and severe dementia at Changhua Christian Hospital, Taiwan. Eleven types of variables from patients with dementia, nine types of variables from patients' caregivers, and 15 types of LTC services were used for this study. The Apriori algorithm was employed to identify the attributes from the patients and their caregivers who used a particular LTC service from a comprehensive viewpoint. Results A total of 75 rules were generated by the Apriori algorithm with support of 2%, confidence of 80%, and lift >1. Among these rules, 25 rules belonged to home personal care services which were summarized further into four general rules for home personal care services. On the other hand, 50 rules belonged to assistive devices that were summarized further into 21 general rules based on their similarities. Patient's walking ability, patient's emotional liability, unemployed or retired caregivers, caregivers' feelings with either helplessness or hopelessness, and caregivers who cared for patients with dementia solely were found to be the critical variables to use home personal care services. In contrast, patient's walking ability, age, and severity as well as caregivers' age, mood, marital status, caregiving burden, and the patient being cared for mainly by a foreign care helper were found to be the critical variables to use assistive devices. Conclusion This study showed preliminary results on the LTC service usage from patients with dementia and their caregivers residing in the community. Understanding the patient–caregiver dyad's profile leads the service providers, policymakers, and the referral team to tailor service provisions better to meet the needs and identify the potential target groups. The findings in this study serve as references to reduce caregivers' burden as well as to improve the quality of care for patients with dementia.